Efeito do cloreto de cádmio sobre as gônadas de girinos de rãs-touro (Lithobates catesbeianus) - Rizzi, Gisele Miglioranza [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
A study about the effects of cadmium chloride (CdCl2) on tadpoles at Gosner stage 25 exposed for 4 and 16 days, to dosage environmentally accepted by National Council on the Environment (CONAMA) for the water classes 1 and 2, was performed. The results showed significant morphological and functional changes. On the ovaries of individuals exposed for 4 days, acceleration in the initial gametogenesis was observed, evidenced by the increased incidence of the number of oocytes in stages I, II and III and increased incidence of micronucleoli, which demonstrates high RNA synthesis. The histochemical and immunohistochemical techniques revealed no relevant changes caused by this trace metal. On the ovaries of individuals exposed for 16 days, acceleration in the initial gametogenesis was also observed, as reported by individuals exposed for 4 days. Immunohistochemistry showed overexpression of HSP70, indicating oxidative stress or physiological adaptive response to CdCl2. On the testicles of individuals exposed for 4 days, there were cases of anatomical changes, cell death, changes in somatic cell death and resorption of the germ cells, degeneration of gonadal tissue, adipogenesis and nonfunctional polygonadism. As noted on the ovaries for this period of exposure, the histochemical and immunohistochemical techniques revealed no relevant changes caused by this trace metal, showing basal expression. On the testes of individuals exposed during 16 days, the acceleration of testicular development was observed, with early primary spermatocytes organizing to form the primary seminiferous ducts, mixed polygonadism, as well as sex reversal. Immunohistochemistry showed no significant differences between the control and exposed groups regarding the expression of HSP70, however it is notable that this expression is below that observed in the group exposed for 4 days. For these reasons, the research shows that the parameters used by CONAMA as doses...

Foi realizado um estudo sobre o efeito do Cloreto de cádmio (CdCl2) em girinos no estágio 25 de Gosner expostos durante 4 e 16 dias à dose ambientalmente aceita pelo Conselho Nacional do Meio Ambiente (CONAMA) para os corpos d´água de classes 1 e 2. Os resultados mostraram mudanças morfofuncionais significantes. Nos ovários dos indivíduos expostos durante 4 dias observou-se a aceleração na gametogênese inicial, evidenciado pelo aumento da incidência do número de ovócitos nos estágios I, II e III e aumento da incidência de micronucléolos, que demonstram alta síntese de RNA. As técnicas histoquímica e imuno-histoquimica não revelaram mudanças relevantes causadas por esse metal traço. Nos ovários dos indivíduos expostos durante 16 dias também observou-se aceleração na gametogênese inicial, como descrito para os indivíduos expostos durante 4 dias. A imuno-histoquimica demonstrou superexpressão da HSP70, indicando estresse oxidativo ou uma resposta adaptativa fisiológica ao CdCl2. Nos testículos dos indivíduos expostos durante 4 dias, observaram-se alterações anatômicas, morte celular, modificações nas células somáticas, morte e reabsorção das células germinativas, além da degeneração do tecido gonadal, adipogênese e poligonadismo não funcional. Como observado nos ovários, para esse período de exposição; as técnicas histoquímica e imuno-histoquimica não revelaram mudanças relevantes causadas por esse metal traço, demonstrando expressão basal. Nos testículos dos indivíduos expostos durante 16 dias observou-se aceleramento do desenvolvimento testicular já observando-se início dos espermatócitos primários organizando-se para formar os ductos seminíferos primordiais, poligonadismo misto, bem como, reversão sexual. A imuno-histoquimica não demonstrou diferenças significantes entre grupo controle e exposto quanto à expressão da HSP70, porém notou-se que esta está abaixo da observada no...
Keywords: Amphibians; Anfíbio; Toxicologia ambiental; Morfologia (Animais); Histoquimica; Rã touro; Gonadas; Girino; Cadmio